2018
DOI: 10.1016/j.ynstr.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Two models of inescapable stress increase tph2 mRNA expression in the anxiety-related dorsomedial part of the dorsal raphe nucleus

Abstract: Expression of TPH2, the rate-limiting enzyme for brain serotonin synthesis, is elevated in the dorsal raphe nucleus (DR) of depressed suicide victims. One hypothesis is that this increase in TPH2 expression is stress-induced. Here, we used an established animal model to address whether exposure to an acute stressor, inescapable tail shock (IS), increases tph2 mRNA and Tph2 protein expression, and if IS sensitizes the DR to a subsequent, heterotypic stressor. In Experiment 1, we measured tph2 mRNA expression 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 95 publications
(132 reference statements)
1
23
0
Order By: Relevance
“…The increase in number of TPH2ϩ neurons in the anhedonic condition (susceptible rats) is consistent with increased TPH2 immunoreactivity and mRNA expression observed after exposure to stress in animals (Poeggel et al, 2003;Amat et al, 2010;Donner et al, 2018) and in brains of depressed patients who committed suicide (Underwood et al, 1999;Boldrini et al, 2005;Bach-Mizrachi et al, 2008). Our findings are the first evidence in an animal model, that stress-induced increase in TPH2 in the DR does not result merely from an increased expression within preexisting serotonergic neurons, but is a result of previously nonserotonergic neurons gaining TPH2 expression.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The increase in number of TPH2ϩ neurons in the anhedonic condition (susceptible rats) is consistent with increased TPH2 immunoreactivity and mRNA expression observed after exposure to stress in animals (Poeggel et al, 2003;Amat et al, 2010;Donner et al, 2018) and in brains of depressed patients who committed suicide (Underwood et al, 1999;Boldrini et al, 2005;Bach-Mizrachi et al, 2008). Our findings are the first evidence in an animal model, that stress-induced increase in TPH2 in the DR does not result merely from an increased expression within preexisting serotonergic neurons, but is a result of previously nonserotonergic neurons gaining TPH2 expression.…”
Section: Discussionsupporting
confidence: 86%
“…Studies in rodent models have shown that serotonergic molecular machinery is upregulated in the DR after both chronic (Adell et al, 1988;Zhang et al, 2012;Donner et al, 2016) and acute stress (Donner et al, 2018). However, they did not specifically address differences between rodents that are susceptible or resilient to chronic stress-induced anhedonia, or whether this upregulation occurs in identified classes of neurons expressing specific neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in rodent models have shown that serotonergic molecular machinery is upregulated in the DR after both chronic (Adell et al, 1988;Zhang et al, 2012;Donner et al, 2016) and acute stress (Donner et al, 2018). However, these studies did not specifically address differences between animals that are susceptible or resilient to chronic stress-induced anhedonia, or whether this upregulation occurs in identified classes of neurons expressing specific neurotransmitters.…”
Section: Discussionmentioning
confidence: 98%
“…The DR and MnR contain the major serotonergic (5-HT) populations (Pollak Dorocic et al, 2014). Both of the nuclei and 5-HT are involved in anxiety and depression, and they are crucial and central drug targets (Lanzenberger et al, 2012;An et al, 2013An et al, , 2016Lopez Hill et al, 2013;Campos et al, 2018;de Souza et al, 2018;Donner et al, 2018). The LC is the major noradrenergic system with regard to stress and major depressive disorder (Chandley and Ordway, 2012;Fan et al, 2018).…”
Section: Emotionmentioning
confidence: 99%